2015
DOI: 10.1155/2015/634175
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperoxaluria Type 1 in 18 Children: Genotyping and Outcome

Abstract: Background. Primary hyperoxaluria belongs to a group of rare metabolic disorders with autosomal recessive inheritance. It results from genetic mutations of the AGXT gene, which is more common due to higher consanguinity rates in the developing countries. Clinical features at presentation are heterogeneous even in children from the same family; this study was conducted to determine the clinical characteristics, type of AGXT mutation, and outcome in children diagnosed with PH1 at a tertiary referral center in Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
4
15
0
1
Order By: Relevance
“…The second most common etiology of CKD in the current study is hereditary renal conditions, including familial focal segmental glomerulosclerosis, congenital nephrotic syndrome, polycystic kidney disease, and primary hyperoxaluria. This finding was also seen in other studies from Oman19, 20 and from the Middle East 9, 11, 21. These findings are expected, as consanguinity is common in these countries.…”
Section: Discussionsupporting
confidence: 87%
“…The second most common etiology of CKD in the current study is hereditary renal conditions, including familial focal segmental glomerulosclerosis, congenital nephrotic syndrome, polycystic kidney disease, and primary hyperoxaluria. This finding was also seen in other studies from Oman19, 20 and from the Middle East 9, 11, 21. These findings are expected, as consanguinity is common in these countries.…”
Section: Discussionsupporting
confidence: 87%
“…The variants in the AGXT gene cause PH1 [ 1 , 27 ], while variants in GRHPR result in PH2 [ 28 , 29 ] and the deficiency in HOGA1 leads to PH3 [ 30 ]. Accordingly, sequencing the whole gene AGXT and detecting the variants has become highly recommended for the diagnosis of PH1 at the earlier stage [ 8 , 11 , 16 ]. Although no confirmed variant hot spots in gene AGXT have been found [ 9 ], more than 190 variants have been reported worldwide in different ethnic populations [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, a six year old boy with confirmed PH1was treated conservatively for five months. Two variant points in gene AGXT were identified in his family by Whole Exon Sequencing (WES), including a novel nonsense variant from his mother and a missense variant from his father [ 6 , 15 , 16 ]. To update PH1 genotypes in Chinese population and elucidate the AGXT variants spectrum in the local population, we built a local reference genome by collecting genomes from 300 healthy Chinese Han people.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, few studies have been conducted on the identification and underlying causes of NC and on whether it has any impact on body growth and renal function in children (10,18). Al-Riyami MS et al found severe renal failure as initial presentation among 39% of children with primary hyperoxaluria type 1 with nephrocalcinosis in comparison with 22% among those without it (19). Hence, the present retrospective study was carried out to examine the causes of NC and its effect on renal function and body growth as well as its follow-up findings in children.…”
Section: Introductionmentioning
confidence: 99%